2000
DOI: 10.1109/20.908342
|View full text |Cite
|
Sign up to set email alerts
|

Conditional ML and MAP techniques for error propagation suppression in multi-path DFE detectors

Abstract: Simple and effective Error Propagation (EP) suppression techniques were reported earlier for decision feedback equalization (DFE) detectors. However, these techniques are not well suited for multi-path DFE detectors because EP suppression and path selection mechanisms interfere with each other. In this paper, we propose novel techniques for improving the EP performance of multi-path DFE schemes, in particular, the (1 7) coded M3DFE (advanced multi-level DFE). The effectiveness of the proposed techniques is qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…First, let us examine TT-1. The false-detection probability for TT-1 is given by for (11) For the sake of simplicity, we neglect the term for in (11) since the typical BER is of the order of or less. Thus, we get…”
Section: A False-detection Probabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…First, let us examine TT-1. The false-detection probability for TT-1 is given by for (11) For the sake of simplicity, we neglect the term for in (11) since the typical BER is of the order of or less. Thus, we get…”
Section: A False-detection Probabilitymentioning
confidence: 99%
“…Third, reliability of the resulting 0018-9464/01$10.00 © 2001 IEEE decisions is assessed by evaluating an appropriate energy function. Very recently, Lin et al [11] reported a threshold-based method for minimizing EP in M3DFE, an advanced version of MDFE.…”
Section: Introductionmentioning
confidence: 99%